2007
DOI: 10.1042/bj20061696
|View full text |Cite
|
Sign up to set email alerts
|

Autophosphorylation-dependent degradation of Pak1, triggered by the Rho-family GTPase, Chp

Abstract: The Paks (p21-activated kinases) Pak1, Pak2 and Pak3 are among the most studied effectors of the Rho-family GTPases, Rac, Cdc42 (cell division cycle 42) and Chp (Cdc42 homologous protein). Pak kinases influence a variety of cellular functions, but the process of Pak down-regulation, following activation, is poorly understood. In the present study, we describe for the first time a negative-inhibitory loop generated by the small Rho-GTPases Cdc42 and Chp, resulting in Pak1 inhibition. Upon overexpression of Chp,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 48 publications
(76 reference statements)
2
47
0
Order By: Relevance
“…Moreover, a recent biochemical analysis demonstrated that Pak interferes with the ability of an exchange factor beta-PIX to activate Rac (ten Klooster et al, 2006), suggesting a function for Pak as an upstream inhibitor of Rac function. Our analysis also fits with the observation that Paks can act downstream of Cdc42 to modulate Rac activation, without their being absolutely required for lamellipodial formation (Cau and Hall, 2005), with observations suggesting that Cdc42 inhibits Pak activity (Weisz Hubsman et al, 2007), and by the presence of both Pak and Cdc42 in a single complex that regulates polarity in yeast (Kozubowski et al, 2008). The effects of Paks on changes in the direction of cell migration, e.g., during neural growth cone turning (Ang et al, 2003;Hing et al, 1999;Newsome et al, 2000), may reflect a similar function for Paks in damping local actin polymerization to facilitate the necessary redistribution of actin filaments.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, a recent biochemical analysis demonstrated that Pak interferes with the ability of an exchange factor beta-PIX to activate Rac (ten Klooster et al, 2006), suggesting a function for Pak as an upstream inhibitor of Rac function. Our analysis also fits with the observation that Paks can act downstream of Cdc42 to modulate Rac activation, without their being absolutely required for lamellipodial formation (Cau and Hall, 2005), with observations suggesting that Cdc42 inhibits Pak activity (Weisz Hubsman et al, 2007), and by the presence of both Pak and Cdc42 in a single complex that regulates polarity in yeast (Kozubowski et al, 2008). The effects of Paks on changes in the direction of cell migration, e.g., during neural growth cone turning (Ang et al, 2003;Hing et al, 1999;Newsome et al, 2000), may reflect a similar function for Paks in damping local actin polymerization to facilitate the necessary redistribution of actin filaments.…”
Section: Discussionsupporting
confidence: 61%
“…Although a PAK1-specific E3 ligase has not been identified, Cdc42 homologous protein (Chp) is a Rho-family GTPase that mediates ubiquitinationdependent degradation of PAK1 (44). A previous report indicated that kinase activity of PAK1 is critical for PAK1 degradation (44). According to this study, Chp could mediate PAK1 degradation only when PAK1 was activated by autophosphorylation on several Ser/Thr residues including S57, S144, S149, S199/S203, and T423.…”
Section: Discussionmentioning
confidence: 99%
“…To understand how PAK1 stabilization is mediated by Tyr phosphorylation, it was important to determine which E3 ligase is responsible for PAK1 degradation. Although a PAK1-specific E3 ligase has not been identified, Cdc42 homologous protein (Chp) is a Rho-family GTPase that mediates ubiquitinationdependent degradation of PAK1 (44). A previous report indicated that kinase activity of PAK1 is critical for PAK1 degradation (44).…”
Section: Discussionmentioning
confidence: 99%
“…RhoV, as well as Cdc42, has been shown to stimulate the ubiquitination and proteasome-mediated degradation of PAK1 in Jurkat T-cells. 36 RhoV interaction with and activation of PAK1 appears to be required for its degradation, based on the effects of RhoV on a range of PAK1 mutants Furthermore, both N-terminal and C-terminal extension regions of RhoV were required to trigger PAK1 degradation, and the N-terminal region was required for PAK1 degradation but not its activation. This suggests a second unknown function for RhoV in PAK1 degradation.…”
Section: Cellular Studiesmentioning
confidence: 99%
“…This suggests a second unknown function for RhoV in PAK1 degradation. 36 In vivo studies RhoV has been described to be involved in developmental processes, although its function appears to differ from RhoU. For example, RhoU and RhoV have different functions in neural crest cells in Xenopus laevis.…”
Section: Cellular Studiesmentioning
confidence: 99%